2017
DOI: 10.1021/acs.jchemed.7b00134
|View full text |Cite
|
Sign up to set email alerts
|

Volcano Plot for Bimetallic Catalysts in Hydrogen Generation by Hydrolysis of Sodium Borohydride

Abstract: In the field of "hydrogen energy", sodium borohydride (NaBH 4 ) is a potential hydrogen carrier able to release H 2 by hydrolysis in the presence of a metal catalyst. Our laboratory experiment focuses on this. It is intended for thirdyear undergraduate students in order to have hands-on laboratory experience through the synthesis of Co−Cu catalysts, X-ray characterization, and catalytic tests to qualitatively illustrate the Sabatier principle (volcano plot). The experiments require minimal preparation and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…As we know, the quantum confinement effect of the 2D nanosheets causes an enlarged bandgap and a blueshifted light absorption edge. [ 47 ] The scattering effect of the porous CNr rod shows an increased absorption of visible light, which is attributed to the light nanosheet assembling structure ( Figure a). [ 48 ] After loading W exp ‐WS on the CNr surface, the light absorption of the W exp ‐WS/CNr composites was further enhanced in the whole band, indicating that W exp ‐WS can promote solar energy utilization of W exp ‐WS/CNr composites.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the quantum confinement effect of the 2D nanosheets causes an enlarged bandgap and a blueshifted light absorption edge. [ 47 ] The scattering effect of the porous CNr rod shows an increased absorption of visible light, which is attributed to the light nanosheet assembling structure ( Figure a). [ 48 ] After loading W exp ‐WS on the CNr surface, the light absorption of the W exp ‐WS/CNr composites was further enhanced in the whole band, indicating that W exp ‐WS can promote solar energy utilization of W exp ‐WS/CNr composites.…”
Section: Resultsmentioning
confidence: 99%
“…Since the early 2000s, many efforts have been dedicated to the hydrolysis of NaBH 4 ; however, there is no consensus about the chemical structure of the by-product [21,22]. Although the majority of the published studies described sodium metaborate (NaBO 2 ) as the by-product of the reaction, several studies reported that the only by-product that forms is sodium tetrahydroxyborate (NaB(OH) 4 ) [21][22][23][24][25][26][27][28][29][30][31][32][33], since the solution is stabilized with pH beyond 11 [3]. Therefore, the appropriate equation would be written as follows:…”
Section: Introductionmentioning
confidence: 99%
“…There is a noteworthy lack of research in recycling, which is a key issue to close the NaBH 4 -H 2 cycle. Therefore, 217 research papers [11,17,20,23,24,[28][29][30][31]50,[52][53][54][55][56][57][58][59][60][61], published from 2014 up to the publication of this paper, were selected to understand the evolution of the research on "hydrogen from NaBH 4 hydrolysis" after the report by Demirci et al [21]. The selected articles were published in peer-reviewed international journals, and all the reviewtype articles and conference proceedings were discarded.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, catalysis is defined as the increase of the chemical reaction rate, using an alternative pathway based on the incorporation of a small quantity of a substance, the catalysts, without being consumed . Catalysis is used in many industrial processes, improving their performance but also transforming them into more sustainable and environmental-friendly processes. Due to both a noteworthy industrial magnitude and crucial sustainable strategy, catalysis should be incorporated and taught at any education level as one of the main fundamentals of Green Chemistry. Although catalysis is already incorporated in most curricula of the main chemistry-oriented universities worldwide, most of the hands-on laboratory experiments are related to organic synthesis catalytic procedures (homogeneous catalysis). Hereby we study a heterogeneous catalytic process for the removal of bromates as an example of hands-on catalytic laboratory experiments and real application of catalysis.…”
Section: Introductionmentioning
confidence: 99%